Recent advances in organic fluorescent probes for detecting phosgene, mustard gas, nerve agents and their mimics - Yang, Yang; Bao, Xiaoying; Shao, Yuxin; Gao, Chao-Ying (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2025)
Chemical warfare agents (CWAs) represent serious threats to national and environmental security. Besides LC-MS and GC–MS, Organic fluorescent probe offers a selective and sensitive tool for identification of CWAs. Utilizing multiple response mechanisms with test strips, sprayer and smartphone enabled rapid, real-time monitoring CWAs. [Display omitted] •The structures of CWAs, their mimics and the lethal content are introduced.•Cyclization, elimination and nucleophilic strategies in sensing phosgene were covered with rapid response times.•Sulphur alkylation for mustard gas and phosphorylation targeting nerve agents provided real-time and on-site detection.•Supramolecular interactions have been exploited for sensitive and selective detection of VX and Novichok. Chemical warfare agents (CWAs) have been notorious for a century, especially sarin and mustard gas, which have produced intolerable menace to civilian lives and environmental security. As a result, developing simple, rapid, portable, sensitive, and selective detection technologies for CWAs is critical. This review primarily covered the recent progress in developing organic fluorescent probes for detecting phosgene, mustard gas, and nerve agents and their mimics. The review mainly discussed various sensing reactions utilized in the covalent strategies like cyclization, elimination, phosphorylation, alkylation, and sprioring-opening reaction, as well as the supramolecular approaches. The comparison of these probes highlighted the successful development of fluorescent probes for CWAs, some with detection limits in nano mol/L in solution and ppb scale in vapor state within seconds. These will contribute to a more effective system for detecting and monitoring CWAs in the future and improve the ability to respond to chemical attacks. Finally, the review discussed the limitations of current probes, emphasizing the need for on-site and real-time detection. It also called for research into new mechanisms and kits for rapid early warning of various CWAs to facilitate emergency handling and decontamination.